2017
DOI: 10.1101/gad.299420.117
|View full text |Cite
|
Sign up to set email alerts
|

GIGYF1/2 proteins use auxiliary sequences to selectively bind to 4EHP and repress target mRNA expression

Abstract: The eIF4E homologous protein (4EHP) is thought to repress translation by competing with eIF4E for binding to the 5 ′ cap structure of specific mRNAs to which it is recruited through interactions with various proteins, including the GRB10-interacting GYF (glycine-tyrosine-phenylalanine domain) proteins 1 and 2 (GIGYF1/2). Despite its similarity to eIF4E, 4EHP does not interact with eIF4G and therefore fails to initiate translation. In contrast to eIF4G, GIGYF1/2 bind selectively to 4EHP but not eIF4E. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
118
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(123 citation statements)
references
References 33 publications
5
118
0
Order By: Relevance
“…GIGYF2 and 4EHP enable the cell to break this cycle by allowing a failed translation event to initiate a specific negative feedback loop which shuts down further translation of the message. Although GIGYF2 and 4EHP have been implicated in translational control in a number of different settings (14,15,19,26,27), our data argue that faulty mRNAs that cause ribosome stalling comprise an important subset of endogenous substrates for GIGYF2 and 4EHP mediated repression. Indeed, we see loss of GIGYF2 stabilizes two distinct classes of stalling reporters.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…GIGYF2 and 4EHP enable the cell to break this cycle by allowing a failed translation event to initiate a specific negative feedback loop which shuts down further translation of the message. Although GIGYF2 and 4EHP have been implicated in translational control in a number of different settings (14,15,19,26,27), our data argue that faulty mRNAs that cause ribosome stalling comprise an important subset of endogenous substrates for GIGYF2 and 4EHP mediated repression. Indeed, we see loss of GIGYF2 stabilizes two distinct classes of stalling reporters.…”
mentioning
confidence: 64%
“…We focused our attention on the second factor, GIGYF2, which has not been previously implicated in the cellular response to damaged messages. Overexpression studies of tagged GIGYF2 have shown that it interacts with the inhibitory cap-binding protein 4EHP (14) and the ubiquitin ligase ZNF598 (15), which is responsible for detecting ribosome collisions and targeting stalled ribosomes to RQC (16,17).…”
mentioning
confidence: 99%
“…Mammalian and Drosophila 4EHPs are required for correct translation control during development (18)(19)(20)(21). Interactions with partner proteins such as Bicoid (16) or GIGYF2 (=GIF2) (22)(23)(24), and with the RISC complex (25,26), have been implicated in induction of mRNA decay and/or translation suppression by 4EHPs. GIGYF2 appears to be able to act both in conjunction with (24), and independently of, 4EHP (27), and interactions with both Ago2 (28) and the CAF1/NOT complex (27) have been documented.…”
Section: Introductionmentioning
confidence: 99%
“…For example, capCLIP may be especially valuable for elucidating the specific biological role(s) of other cellular cap-binding proteins, particularly the eIF4E2 (4EHP) and eIF4E3, the other two cytoplasmic cap-binding proteins in mammals. While eIF4E2 is generally thought to play a role in translational repression (see, for example (59,60)), other work suggests eIF4E2 promotes mRNA translation in certain cellular contexts (61). As capCLIP makes no assumptions about the cellular role of a cap-binding protein, it is an ideal method for elucidating eIF4E2 function.…”
Section: The Way Forward For Capclip and Future Prospectsmentioning
confidence: 99%